Parasitic nematode-induced CD4+Foxp3+T cells can ameliorate allergic airway inflammation. - Shin Ae Kang; Mi-Kyung Park; Min Kyoung Cho; Sang Kyun Park; Min Seong Jang; Bo-Gie Yang; Myoung Ho Jang; Dong-Hee Kim; Hak Sun Yu (Public Library of Science (PLoS), 2014)
The recruitment of CD4+CD25+Foxp3+T (Treg) cells is one of the most important mechanisms by which parasites down-regulate the immune system.We compared the effects of Treg cells from Trichinella spiralis-infected mice and uninfected mice on experimental allergic airway inflammation in order to understand the functions of parasite-induced Treg cells. After four weeks of T. spiralis infection, we isolated Foxp3-GFP-expressing cells from transgenic mice using a cell sorter. We injected CD4+Foxp3+ cells from T. spiralis-infected [Inf(+)Foxp3+] or uninfected [Inf(-)Foxp3+] mice into the tail veins of C57BL/6 mice before the induction of inflammation or during inflammation. Inflammation was induced by ovalbumin (OVA)-alum sensitization and OVA challenge. The concentrations of the Th2-related cytokines IL-4, IL-5, and IL-13 in the bronchial alveolar lavage fluid and the levels of OVA-specific IgE and IgG1 in the serum were lower in mice that received intravenous application of Inf(+)Foxp3+ cells [IV(inf):+(+) group] than in control mice. Some features of allergic airway inflammation were ameliorated by the intravenous application of Inf(-)Foxp3+ cells [IV(inf):+(-) group], but the effects were less distinct than those observed in the IV(inf):+(+) group. We found that Inf(+)Foxp3+ cells migrated to inflammation sites in the lung and expressed higher levels of Treg-cell homing receptors (CCR5 and CCR9) and activation markers (Klrg1, Capg, GARP, Gzmb, OX40) than did Inf(-)Foxp3+ cells.T. spiralis infection promotes the proliferation and functional activation of Treg cells. Parasite-induced Treg cells migrate to the inflammation site and suppress immune responses more effectively than non-parasite-induced Treg cells. The adoptive transfer of Inf(+)Foxp3+ cells is an effective method for the treatment and prevention of allergic airway diseases in mice and is a promising therapeutic approach for the treatment of allergic airway diseases.